Estimation of the Standard Atmospheric Earth Model Parameters at 86 km Altitude - Hussein, Hussein Omran; Yaseen, Waleed Ibrahim (Iraqi Journal of Science, 2023)
Utilizing the Turbo C programming language, the atmospheric earth model is created from sea level to 86 km. This model has been used to determine atmospheric Earth parameters in this study. Analytical derivations of these parameters are made using the balancing forces theory and the hydrostatic equation. The effects of altitude on density, pressure, temperature, gravitational acceleration, sound speed, scale height, and molecular weight are examined. The mass of the atmosphere is equal to about 50% between sea level and 5.5 km. g is equal to 9.65 m/s2 at 50 km altitude, which is 9% lower than 9.8 m/s2 at sea level. However, at 86 km altitude, g is close to 9.51 m/s2, which is close to 15% smaller than 9.8 m/s2. These results have been compared with an international standard atmosphere. The presumed atmosphere model differs significantly from the actual atmosphere because weather fluctuations are not taken into consideration in this model.